2016
DOI: 10.1007/s00232-016-9891-4
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Cisplatin Electrochemotherapy on Human Neuroblastoma Cells

Abstract: Electrochemotherapy is the usage of electroporation to introduce chemotherapeutic drugs through membrane pores into target cells for cancer treatment. The effectiveness of chemotherapeutic drugs would be increased dramatically when they are used in electrochemotherapy than standard chemotherapy. In the present study, we investigated the effects of cisplatin treatment with electroporation on human SH-SY5Y neuroblastoma cells. SH-SY5Y cells were treated with different concentrations (0.15-24 µg/mL) of cisplatin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 25 publications
0
11
0
1
Order By: Relevance
“…The reasons for difference in response are multifaceted and include physical features pertinent to electrochemotherapy, such as unavailability of the drug and insufficient coverage with electric field and biological, pertinent to patient, such as previous treatments, difference in tumor microenvironment, mutational status, and so on. 2,14,18 Thus, electrochemotherapy is still evaluated in different types of cancer, either in vitro or in vivo, including colon carcinoma CT26 (in vitro) 19 ; bladder cancer SW780 (in vitro and in vivo) 20 ; fibroblasts, human umbilical vein endothelial cells (HUVEC; in vitro) and two squamous cell carcinomas, CAL-27 and SCC-4 (in vitro) 21 ; ovarian cell lines OvBH-1 and SKOV-3 (in vitro) 22 ; human neuroblastoma SH-SY5Y cells (in vitro) 23 ; BRAF-mutated melanoma cells (SK-MEL-28) and their counterpart without mutation, CHL-1 cells (in vitro) 24 ; chemoresistant uveal melanoma cells (Mel 270, 92-1, OMM-1, OMM-2) (in vitro) 25 ; primary cells from metastatic pancreatic tumors (in vitro) 26 ; human papillomavirus (HPV)-positive head and neck squamous cell carcinoma 2A3 (in vitro and in vivo) 27 ; Lewis lung carcinoma and CT 25 colorectal carcinoma (in vivo) 28 ; conjunctival melanoma CRMM1 and CRMM2 and normal conjunctival epithelial cells HCjE-Gi (in vitro) 29 ; radioresistant head and neck squamous cell carcinoma Fa-DuRR (in vitro and in vivo) 30 ; and small cell lung cancer H69AR cells (in vitro). 31 In general, it was demonstrated that electrochemotherapy with bleomycin or cisplatin causes immunogenic cell death in colon carcinoma 19,28 ; that human endothelial cells are more susceptible to electrochemotherapy than tumor cells, 21 supporting the antivascular effect in vivo; that electrochemotherapy is effective in ovarian carcinoma cells resistant to standard therapy 22 ; and that electrochemotherapy is also effective in neuroblastoma and primary pancreatic tumor cells, which was not demonstrated before.…”
Section: Electrochemotherapy: New Tumor Entities and New Combinationsmentioning
confidence: 99%
See 1 more Smart Citation
“…The reasons for difference in response are multifaceted and include physical features pertinent to electrochemotherapy, such as unavailability of the drug and insufficient coverage with electric field and biological, pertinent to patient, such as previous treatments, difference in tumor microenvironment, mutational status, and so on. 2,14,18 Thus, electrochemotherapy is still evaluated in different types of cancer, either in vitro or in vivo, including colon carcinoma CT26 (in vitro) 19 ; bladder cancer SW780 (in vitro and in vivo) 20 ; fibroblasts, human umbilical vein endothelial cells (HUVEC; in vitro) and two squamous cell carcinomas, CAL-27 and SCC-4 (in vitro) 21 ; ovarian cell lines OvBH-1 and SKOV-3 (in vitro) 22 ; human neuroblastoma SH-SY5Y cells (in vitro) 23 ; BRAF-mutated melanoma cells (SK-MEL-28) and their counterpart without mutation, CHL-1 cells (in vitro) 24 ; chemoresistant uveal melanoma cells (Mel 270, 92-1, OMM-1, OMM-2) (in vitro) 25 ; primary cells from metastatic pancreatic tumors (in vitro) 26 ; human papillomavirus (HPV)-positive head and neck squamous cell carcinoma 2A3 (in vitro and in vivo) 27 ; Lewis lung carcinoma and CT 25 colorectal carcinoma (in vivo) 28 ; conjunctival melanoma CRMM1 and CRMM2 and normal conjunctival epithelial cells HCjE-Gi (in vitro) 29 ; radioresistant head and neck squamous cell carcinoma Fa-DuRR (in vitro and in vivo) 30 ; and small cell lung cancer H69AR cells (in vitro). 31 In general, it was demonstrated that electrochemotherapy with bleomycin or cisplatin causes immunogenic cell death in colon carcinoma 19,28 ; that human endothelial cells are more susceptible to electrochemotherapy than tumor cells, 21 supporting the antivascular effect in vivo; that electrochemotherapy is effective in ovarian carcinoma cells resistant to standard therapy 22 ; and that electrochemotherapy is also effective in neuroblastoma and primary pancreatic tumor cells, which was not demonstrated before.…”
Section: Electrochemotherapy: New Tumor Entities and New Combinationsmentioning
confidence: 99%
“…31 In general, it was demonstrated that electrochemotherapy with bleomycin or cisplatin causes immunogenic cell death in colon carcinoma 19,28 ; that human endothelial cells are more susceptible to electrochemotherapy than tumor cells, 21 supporting the antivascular effect in vivo; that electrochemotherapy is effective in ovarian carcinoma cells resistant to standard therapy 22 ; and that electrochemotherapy is also effective in neuroblastoma and primary pancreatic tumor cells, which was not demonstrated before. 23,26 Furthermore, it was demonstrated that electrochemotherapy with cisplatin is a promising therapeutic approach for bladder cancer 20 and that it is more effective in HPV-positive than HPV-negative head and neck tumors. 27 For electrochemotherapy with bleomycin, it was demonstrated that it is more effective in melanoma cells that harbor BRAF mutation 24 and in melanoma cells that are chemoresistant.…”
Section: Electrochemotherapy: New Tumor Entities and New Combinationsmentioning
confidence: 99%
“…Elektrokemoterapinin başlangıçta kutonöz ve subkutonöz tümörlerin tedavisinde ve palyatif tedavi seçeneği olarak kullanılırken, teknolojideki ilerlemeler sonucunda internal tümörlerin tedavisinde de kullanılabilir olduğu belirtilmektedir. (4,6,11) Literatürde elektrokemoterapinin klinik olarak ilk kez metastatik (16) Günümüzde meme kanseri (11) , hepatosellüer karsinoma (17) , pankreas kanseri (18,19) , akciğer kanseri (20) , böbrek kanseri (21,22) , prostat kanseri (23,24) , nöroblastoma (25) gibi farklı histolojik yapılardaki kanserlerin tedavisinde elektrokemoterapi işleminin başarılı bir şekilde uygulandığı belirtilmektedir.…”
Section: Elektrokemoterapinin Klinik Uygulama Alanlarıunclassified
“…The biology of apoptosis has been studied by using this cell line with cisplatin to model the hair cells of the inner ear. 42-44…”
mentioning
confidence: 99%